Tensile nanostructured hierarchically porous non-precious transition metal-based electrocatalyst for durable anion exchange membrane-based water electrolysis - Singh, Kailash; Selvaraj, Kaliaperumal (Journal of Colloid and Interface Science, 2024)
Electrochemical water electrolysis is a promising method for sustainable hydrogen production while transiting towards hydrogen economy. Among many, the Anion Exchange Membrane (AEM) based water electrolyzer is an emerging yet potentially affordable technology on maturity for producing large-scale hydrogen accommodating the usage of Non-Platinum Group Metal (non-PGM) based inexpensive electrocatalysts. Herein, we demonstrate the excellent performance of a bifunctional Nickel Copper Phosphide-Nickel sulphide (NCP-NS) electrocatalyst with a unique tensile nanostructure obtained via a facile, controlled ambient galvanic displacement route. An AEM electrolyzer with a larger active area of 10 cm(2) stacked with the symmetric NCP-NS electrodes and a membrane demonstrates scalability with a requirement of a mere 1.66 V to reach a current density of 10 mA cm(-2). The nickel-copper phosphide boosts the kinetics of charge transfer between the electrode and electrolyte interface, while a unique combination of a few nickel sulphide phases present in the catalyst provides sufficiently appropriate active sites for the overall water electrolysis. For the first time, we report a room temperature performance of similar to 230 mA cm(-2) at 2 V for a non-PGM-based bifunctional electrocatalyst with exceptional durability for over 300 h of operation in an AEM water electrolyser with a retention rate of 95 %-97 % at a current density range of 80-800 mA cm(-2).
Keywords: AEM electrolyzer; Bifunctionality; Electrodeposition; Non-PGM based Electrocatalyst; stability

Chlorophobic iron hydrogen phosphite as OER-active electrocatalyst in anion exchange membrane (sea)water electrolysis - Das, Chandni; Sinha, Nibedita; Nair, Aathira; Pal, Santanu; Joshi, Kavita; Roy, Poulomi (Small, 2025)
Seawater electrolysis is recognized as a promising technology to cater to the worldwide drive for sustainable hydrogen production; however, its practical viability is often hindered by the inevitable anode corrosion arising from the electrode side reactions owing to the presence of high chloride content which eventually degrade the electrode performance eventually. Herein, the design of unprecedented ammonium iron hydrogen phosphite (FeHPhi) along with a trace amount of Cu, is reported as the unique and much desired electrode material for seawater electrolysis due to its special chloride repellant nature along with great electrocatalytic activity toward water oxidation. The [HPO3](2-) oxoanion as Lewis base in the structure effectively restricts chloride ions, while the Fe center acts as Lewis acid offering an active site for water oxidation, also well-supported theoretically. Leveraging this frustrated Lewis pair combination, the electrocatalyst achieves a high current density of 500 mA cm(-2) at 344 mV overpotential in alkaline real seawater with impressive robustness to sustain for 200 h when operated under chlorine evolution reaction dominating region (>2 V). The electrocatalyst also demonstrates superior performance in anion exchange membrane freshwater and seawater electrolysis, demonstrating its potential applicability.
Keywords: AEM electrolyzer; chloride repellant; electrocatalyst; hydrogen production; seawater oxidation

Dynamic and resilient cobalt copper nitride and iron nitride heterostructure aided energy economic urea electrolysis in anion exchange membrane electrolyzer - Sinha, Nibedita; Das, Chandni; Er, Chen-Chen; Urkude, Rajashri R.; Pal, Santanu; Ghosh, Biplab; Chai, Siang-Piao; Roy, Poulomi (Small, 2026)
Urea oxidation reaction (UOR) is recognized for energy-efficient hydrogen production, which nonetheless requires a meticulously designed electrocatalyst with active sites for intermediates adsorption and gaseous products desorption to fully exploit its advantages. Herein, we design the heterostructure consisting of cobalt copper nitride and iron nitride (Co3CuN/FexNy) as an efficient and trifunctional electrocatalyst, which requires 1.35 VRHE, 1.55 VRHE, and 0.23 VRHE potentials to reach 100 mA cm-2 current density for UOR, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER), respectively. Unlike the conventional UOR selective electrocatalyst, Co3CuN/FexNy not only facilitates the UOR -> OER switching but also shows self-regulatory ability in UOR <-> OER. The Density Functional Theory (DFT) study explained that while Co3CuN promoted the adsorption of CO(NH2)2 and H2O, FexNy facilitated CO2 and N2 desorption, resulting in accelerated UOR and HER kinetics. The electrocatalyst also demonstrated outstanding performance in a urea-coupled AEM electrolyzer with about 20% of power saving and great electrolyzer efficiency, further highlighting its potential for industry-relevant applications.
Keywords: AEM electrolyzer; heterostructured electrocatalyst; reversible adaptability; urea oxidation; Water oxidation